The improvement of the quality assessment and cryopreservation methods in Volga pikeperch (Sander volgensis) sperm obtained from the Lake Balaton for practical and conservation purposes - Nagy, Borbála; Várkonyi, Levente; Fodor, Ferenc; Koltai, Tamás; Bodnár, Ádám; Molnár, József; Láng, Levente Zete; Izsák, Tibor; Staszny, Ádám; Ferincz, Árpád; Birkó-Sulyok, Zita Katalin; Urbányi, Béla; et al. (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
Sperm cryopreservation in Volga pikeperch (Sander volgensis) can simplify the propagation process and reduce the costs of the broodstock management. The method can help also the reintroduction of the natural populations in Volga pikeperch. In our study, 3 different experiments were carried out to improve the sperm sampling (regular stripping method, catheter, stripping into Pike extender and squeezing of the testis) and cryopreservation methods extenders (Extenders: modified Tanaka, Pike and Glucose, Straws: 0.5 and 5 mL) (N=39) in Volga pikeperch. The progressive motility in both fresh and the cryopreserved samples was recorded with Computer-assisted Sperm Analysis (CASA). According to our results, the regular, catheter stripping and squeezing testis can be effectively applied in Volga pikeperch. However, squeezed testis provides the highest volume of sperm. Both cryopreservation methods (0.5 and 5 mL straws) using modified Tanaka extender were efficiently used in hatchery conditions.